ARACOV-02. Specialized nutritional intervention and telerehabilitation in patients with long COVID: Protocol of a randomized controlled trial. - Beatriz Carpallo-Porcar; Carolina Jiménez-Sánchez; Sandra Calvo; Pilar Irún; Elena Kolesnyk-Sumskaya; Ana Isabel Aller-Blanco; Esther Del Corral Beamonte (PLoS ONE)
Background It is estimated that at least 10% of the population infected with SARS-CoV-2 develop Post COVID Condition, which is characterized by a diverse array of symptoms including dyspnea, fatigue, anxiety, depression, and deterioration in quality of life. The SARS-CoV-2 virus can trigger an excessive immune response, characterized by the release of pro-inflammatory cytokines including IL-6, IL-1, TNFα and reactive oxygen species. Specialized Pro Resolving Mediators (SPMs) (17-HAD, 14-HAD and 18_HEPE) that could be useful in Post COVID Condition modulating the inflammatory response. The objective is to determine the change in quality of life, inflammatory profile, functional capacity and emotional variables in a group taking a nutritional supplement (SPMs) plus a telerehabilitation programme. Methods ARACOV-2 study is a double-blind, parallel-group, randomized control trial with two parallel interventions: Nutritional supplement and telerehabilitation vs placebo supplement and telerehabilitation. The primary endpoint will be quality of life (EQ-5L-5D). The intervention will last 12 weeks with a daily intake of omega-3 or placebo and a daily supervised rehabilitation programme using telerehabilitation. Discussion This study suggests that SPMs supplementation combined with telerehabilitation may improve inflammation and symptoms like fatigue in Post COVID Condition patients. Both interventions have anti-inflammatory potential, and their combined use could enhance physical and mental health outcomes. This approach offers a promising strategy for managing Post COVID Condition symptoms. Trial registration ClinicalTrials.gov NCT06063031.